Roles of the students and teachers in distance education - Îşman, Aytekin; Altinay, Zehra; Altinay, Fahriye (My University, 2004)
Distance Education is the new, global technology based education to facilitate easy, immediate learning and interaction for all communicators who are the teachers and students that involve the education program. Distance Education can provide wide-mass education for everyone, it leads people to learn individually and let responsibility of learning to the people. In addition to this; it is obvious to select courses and content that reflect the concerning needs and motivation of students. It provides creative and qualified ideas atmosphere and information that will be presented should be update and interesting for all different kinds of students according to their backgrounds information. For the effective distance education programs out of the communicational or any kind of barriers, there should be consciousness on the definable roles of the teachers and students in learning-teaching process.
Keywords: Distance Education; Distance Educator; Role of Students; Teacher in Distance Education; Turkey